Steel plate shear walls with large disconnected lengths of web plate to vertical boundary element. (December 2021) - Hajimirsadeghi, Mohammad Reza; Fanaie, Nader
Abstract: Steel plate shear walls as lateral load resisting systems provide resistance to seismic and wind forces in buildings. The partial length connection web plate to vertical boundary element steel plate shear walls, which lacks the connection at the middle height of VBE has been recently introduced by researchers. This novel steel shear wall was proposed as a key approach so as to reduce column's significant demand due to resistance of web plate diagonal yielding in conventional steel plate shear walls. In this survey the design of the proposed shear walls with regard to large value of not connected length ratio of web plate to vertical boundary element was considered. Development of the tension field action across the entire width of the proposed shear walls considering different panel aspect ratios and various number of stories were investigated by establishing 27 numerical models (3 groups of 9 groups) using finite element Abaqus software. The available experimental data was used to validate the modeling methodology. The pushover analyses were performed for all the models. Finally, based on the presented numerical investigation, the equations governing the system, including panel shear strength and the angle of inclination of the tensile field, which are valid for not connection length ratio larger than thirty percent, were analytically developed.